Software engineering a practitioner's approach - Pressman, Roger S. (McGraw-Hill, 1982)
This indispensable guide to software engineering exploration enables practitioners to navigate the ins and outs of this rapidly changing field. Pressman's fully revised and updated Fourth Edition provides in-depth coverage of every important management and technical topic in software engineering. Moreover, readers will find the inclusion of the hottest developments in the field such as: formal methods and cleanroom software engineering, business process reengineering, and software reengineering.